PENGGUNAAN PERPUSTAKAAN DALAM PROGRAM GERLIMA DI MADRASAH TSANAWIYAH NEGERI (MTSN) 1 JOMBANG - Nasucha, Riza Umami; Muslih, Imam; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
The literacy movement program promoted by the Ministry ofEducation and Culture aims to inspire the public, especially students, to comeread books in the library. This study aims to determine the use of libraries in themadrasa literacy movement program in MTsN 1 Jombang but also aims to fosterthe interest and enthusiasm of students in literacy activities, especially reading inthe library. The research approach uses descriptive qualitative, and the type ofresearch is a case study. Data collection techniques used are observation,interviews, and documentation. Data analysis using models from Miles and Huberman consisted of data reduction, data presentation, and conclusion making.The results of the study explained that in attracting students' enthusiasmregarding the use of libraries a madrasa literacy movement program was created.The program implemented at MTsN 1 Jombang is the reading activity programin the library and the GERLIMA (Madrasah Literacy Movement) program. Inthe program, students are encouraged to carry out literacy activities in the library.